The Role of Mediation in Resolving Civil Law Disputes in Indonesia - Flora, Henny Saida; Ginting, Grenaldo; Ganap, Nita Cicilia; Simamora, Pinta N. S.; Burhanuddin, Ahmad (Jurnal Smart Hukum (JSH), 2025)
The utilisation of mediation as a mechanism for the resolution of civil law disputes in Indonesia has become increasingly significant, representing an alternative to the frequently protracted, expensive, and adversarial litigation process. Mediation, a form of alternative dispute resolution (ADR), adopts a collaborative and amicable approach by facilitating dialogue between disputing parties with the assistance of a neutral third party. This study aims to examine the role and effectiveness of mediation within Indonesia's civil law framework, with a focus on its legal foundation and practical implementation. A qualitative research methodology was employed to analyse the recent scholarly literature, legal documentation and case studies, in order to draw conclusions on the impact of this process on a range of civil disputes, including those arising from family law, commercial conflicts and disputes relating to land ownership.The findings indicate that mediation has a number of significant advantages, including the expediting of dispute resolution, the reduction in legal expenses and the preservation of relationships between disputants, thereby alleviating the burden on Indonesia's overburdened judicial system. However, despite the evident benefits, the adoption of mediation in Indonesia faces considerable challenges. These challenges encompass a paucity of public awareness, inadequate mediator training and cultural perceptions that favour litigation over other solutions.